PENGARUH VARIASI WAKTU PENGERINGAN OVEN TERHADAP KARAKTERISTIK FISIK AMILUM TALAS KIMPUL (Xanthosoma sagittifolium) - Saraswati, Luh Ayu Putri; I Gusti Ngurah Agung Dewantara Putra (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Starch is a polysaccharide carbohydrate which has inert, so it’s widely used as an excipient in the pharmaceutical industry. Starch is found in many organs in plants that serve as place to store the food reserves, one of which is the cocoyam (Xanthosoma sagittifolium), which in its tubers contains about 36% starch with quite high amylose and amylopectin content, namely 15.4% and 81.5%. The length of drying time results in different physical characteristics of starch, so it takes the right time to produce good physical characteristics of starch and according to requirements. The evaluation tests were carried to find out the physical characteristics of cocoyam, namely organoleptic test, identification test, microscopic test, water content test, and pH test. The result obtained that 1 day drying time can produce starch with good physical characteristics and according to requirements.